Pendidikan Karakter dalam Pembiasaan Ibadah Shalat Siswa SDN Tanjung Pura III dan MDTU Darul Fatwa - Azhari Ardiansyah Nur Soleh; Ajat Rukajat; Khalid Ramdhani (ISLAMIKA, 2022)
Character can be defined as how to apply or engrave the value of goodness in the form of actions or behavior, so that people who are dishonest, cruel, greedy, and behave badly are said to have bad character. On the other hand, people whose behavior is in accordance with moral rules are called people of noble character. In cultivating character education, it is necessary to have awareness from various parties to start and become habitual. In this regard, this study aims to reveal the values of character education that were developed on the values of character education in increasing prayer. The approach used in this research is a descriptive qualitative approach. The data of this research is the application of character education in improving prayer worship. The process of collecting data using the method of observation, interviews and documentation. After the data is collected, it is then analyzed using verification analysis techniques. From the analysis that has been carried out, it is then presented with the reduction method. From the analysis that has been carried out, it is then presented using the selection method. The presentation of the results of data analysis was carried out by observation, interviews and documentation. The results showed that the values of character education that were revealed in the application of character education in improving students' prayer worship the values found were: (1) religious, (2) honest, (3) tolerance, (4) hard work, (5) curiosity, (6) friendly/communicative, (7) responsibility and the value of findings, namely the value of good habits for praying. Based on the results of this study, the authors suggest to principals and teachers, in order to teach the values of character education in improving prayer, students are formed who have character and always perform prayers.